Process optimisation and techno-economic analysis of briquette production from corn-stover - Ngubane, Nqobile Felicia (Cape Peninsula University of Technology, 2021)
The world is currently challenged with an energy crisis associated with global warming, and environmental pollution caused by the increase of global population and industrial activities. Renewable energy sources such as biomass is an alternative source of fuel to traditional fossil fuel sources and their use could be an important contributor in satisfying South Africa’s growing energy demand. Biomass usually consists of an animal, forest, and agricultural residues. South Africa being the largest producer of maize (corn) in Africa generates approximately 5.1 million metric tonnes of corn residues per annum as agricultural wastes remain untapped. This is a potential renewable feedstock that is sustainably available with no competition for resources with no food/feed production. This study aimed to add value to corn-stover (CS) by converting it into an eco-friendly solid fuel (briquettes) with high carbon content and high calorific value (HHV) to meet the increasing energy demand in South Africa through slow pyrolysis and densification process. This work investigated biochar and char briquettes in terms of its ultimate and proximate analyses. Moreover, a statistical optimisation tool, central composite design (CCD) was used to maximise the production of high-quality briquettes, in terms of HHV, compaction pressure, durability, and density. Furthermore, the optimised conditions were used to develop a process design and economic evaluation of a briquette production scale-up plant. The results indicate that the HHV (25.5-28.81 MJ/kg) of the briquettes was only influenced by binder concentration. Whereas the compressive strength (3.45-6.11 N/mm2) and density (420-788 kg/m3) of the briquettes were both influenced by compaction pressure and binder concentration. Finally, the results show that all 3 factors influenced the durability (97-100%) of the briquettes. Therefore, under these optimised conditions compression pressure (40MPa), binder concentration (8.74%) and drying temperature (21.6 ºC), HHV, compressive strength, density and durability as predicted by the respective developed models are 27.32 MJ/kg, 5.48 N/mm2, 770.40 m3/kg and 98.87% respectively. These briquettes were comparable to that of domestic char bio-briquettes made from wood, and South African bituminous A grade coal used for domestic and industrial purposes. Techno-economic analysis of 550 kg/h of CS briquetting plant showed that it was able to generate 300 kg/h of dry briquettes. The economic evaluation of this study showed that with a total capital investment (TCI) of $518 790.68 the plant was found to be economically feasible with a DBPB <4 years and DCFROR >30%. Although this study is seen to be technically and economically profitable, the goals and environmental surroundings of the project should be decided based on the location and availability of feedstock.
Thesis (MEng (Chemical Engineering))--Cape Peninsula University of Technology, 2021
Keywords: Briquets (Fuel); Corn stover as fuel; Agricultural wastes -- Recycling; Biomass energy; Renewable energy sources; Energy crops